2017
DOI: 10.1021/acs.inorgchem.7b02143
|View full text |Cite
|
Sign up to set email alerts
|

Coordinatively Unsaturated Metal–Organic Frameworks M3(btc)2 (M = Cr, Fe, Co, Ni, Cu, and Zn) Catalyzing the Oxidation of CO by N2O: Insight from DFT Calculations

Abstract: The oxidation of CO by NO over metal-organic framework (MOF) M(btc) (M = Fe, Cr, Co, Ni, Cu, and Zn) catalysts that contain coordinatively unsaturated sites has been investigated by means of density functional theory calculations. The reaction proceeds in two steps. First, the N-O bond of NO is broken to form a metal oxo intermediate. Second, a CO molecule reacts with the oxygen atom of the metal oxo site, forming one C-O bond of CO. The first step is a rate-determining step for both Cu(btc) and Fe(btc), where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 70 publications
(88 reference statements)
4
57
0
Order By: Relevance
“…On the basis of the work of Ye and Liu, 515 Ketret et al. 516 performed a DFT mechanistic study on M 3 (btc) 2 MOFs (btc = benzene-1,3,5-tricarboxylate, M = Cr, Fe, Co, Ni, Cu, and Zn) to evaluate their suitability to oxidize CO with NO 2 . This study was based on the efficient CO oxidation catalyzed by several MOFs, including Cu 3 (btc) 2 .…”
Section: Mechanistic Complexity In Catalysis By 3d Transition Metalsmentioning
confidence: 99%
“…On the basis of the work of Ye and Liu, 515 Ketret et al. 516 performed a DFT mechanistic study on M 3 (btc) 2 MOFs (btc = benzene-1,3,5-tricarboxylate, M = Cr, Fe, Co, Ni, Cu, and Zn) to evaluate their suitability to oxidize CO with NO 2 . This study was based on the efficient CO oxidation catalyzed by several MOFs, including Cu 3 (btc) 2 .…”
Section: Mechanistic Complexity In Catalysis By 3d Transition Metalsmentioning
confidence: 99%
“…1. According to the available research experiences, considering the calculation cost, the models could be cut from the periodic structure and saturated with protons so that the overall charge remains zero in the whole process of mechanistic exploration [48][49][50][51][52][53]. The effectiveness of the Cu 2 (HCOO) 4 model A has been validated in our group by two different models (see B and C in Fig.…”
Section: Modelsmentioning
confidence: 97%
“…It is found that these materials can be served as promising catalysts for N 2 O decomposing to N 2 and a dissociated oxygen atom. Sombat et al [19] explored the catalytic effects of metal organic structure (MOF) M 3 (BTC) 2 (M = Fe, Cr, Co, Ni, Cu and Zn) on the oxidation of CO by N 2 O, and found that the order of the catalytic reaction rate is: Cr 3 (BTC) 2 > Fe 3 (BTC) 2 > Co 3 (BTC) 2 > Ni 3 (BTC) 2 > Cu 3 (BTC) 2 < Zn 3 (BTC) 2 . The theoretical and experimental study of the decomposition of N 2 O on the bimetallic catalyst Rh-M (M = Co, Ni, Cu) had been carried by Hao Chen et al [20], and it showed that the catalytic activity trend of the Rh–M catalyst is determined as Rh 7 Co 1 /SBA-15 > Rh/SBA-15 > Rh 7 Ni 1 /SBA-15 > Rh 7 Cu 1 /SBA-15.…”
Section: Introductionmentioning
confidence: 99%